B.R. AMBEDKAR AND INDIAN SOCIETY - Dr. Karnika Dubey (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Dr Ambedkar was a great patriot, renowned social intellectual, orator, politician and dynamic essayist. He was a scholar who scrutinized all the political, social and economic and cultural practices that broadened the awareness for human development. He is the live-streaming spirit of India’s constitution. He advocated for the inclusion of the groups which were abused, discouraged and marginalized. He was a unique crucifying spirit, who cut himself out in this way to launch the important socialventures to herald principal developmental changes in society. Like a pioneering engineer of social values and ethics. Ambedkar pared the way of the Fair Indian Republic. He had played a distinctively exceptional rolein the making of the future social framework of Indian heritage.